READING MISCUE ANALYSIS OF THE 12 th GRADE STUDENTS OF SMAN 01 SUMBERPUCUNG MALANG - PUTRI, HANDITA PRATAMA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Reading, Miscue Analysis, Types of Miscue, Factor Contributing Miscue Production. Reading is one of the language skills that is important to be mastered beside listening, speaking, and writing. Miscue analysis is a method which attempts to analyze the unexpected responses of unfamiliar text which occurs in oral reading. Reading miscue analysis is a tool for looking closely at the types of reading strategies a reader uses. Retrospective Miscue Analysis (RMA) was used in this research which comprised reading text aloud, retelling and discussion session. This research intended to investigate reading miscue analysis by 12th grade students of SMAN 01 Sumberpucung Malang. There were two aims in this research. The first was to find out what the types of reading miscue produced by the 12th grade students of SMAN 01 Sumberpucung Malang. The second was to find out what the possible factors contributing to reading miscue produced by the 12th grade students of SMAN 01 Sumberpucun Malang.This research used qualitative approach. In achieving the purpose of the research, the researcher applied theories of Types of Miscue proposed by Goodman and Burke (1973) and Factors Contributing Miscue Production proposed by Kern (1988). The data were originated from all utterances of four participants. The data were taken by recording process and they were changed into transcription.The result showed that all participants who consisted of four students produced 74 (63%) substitution miscues, 21 (17%) omission miscues, 10 (8%) correction miscues, 9 (7%) repetition miscues, and 5 (4%) insertion miscues. Then, the result of factors contributing miscue production showed that two participants were influenced by linguistic factors and cognitive factors. Meanwhile, the other two participants were influenced by linguistic factors, cognitive factors, and affective factors.The researcher suggests for the further researchers who want to conduct a study about RMA to use more than two theories and from other theories to gain more information about RMA. Then, English teachers have to develop their strategies of teaching reading and speaking for their students. The last suggestion is dedicated for students to enrich their vocabularies by reading and speaking in English.